Analysis of The Effects of Service Delivery on The Wellbeing of Internally Displaced Persons (IDPS) in Federal Capital Territory (FCT), Abuja - Idowu, Olusegun O; Martins, Valda; Santali, Ndako B; Adama, Jonathan U; Adeogun, Adekunle S; Danlami, Gideon (UI Scholars Hub, 2024)
The provision of services, encompassing substandard medical facilities, inadequate housing conditions, limited access to electricity, insufficient recreational amenities, and the absence of potable water supply, has emerged as a significant impediment confronting Internally Displaced Persons (IDPs) both domestically and globally. The present investigation sought to evaluate the impact of service delivery on the welfare of IDPs residing in the Federal Capital Territory (FCT), Abuja. The objectives of this inquiry were to assess the socioeconomic attributes of the IDPs, scrutinize the types and efficacy of service delivery within the IDP camps, and appraise the consequences of service delivery on the well-being of the IDPs in the research area. For this study, we selected a representative sample of 331 households to examine the households encompassing the IDPs. The data underwent statistical analysis employing the Statistical Package for Social Sciences (SPSS). The findings unveiled the extent of deprivation endured in terms of essential amenities such as shelter, proper sanitation, reliable electricity, potable water, and adequate healthcare provisions. For instance, all participants resided in makeshift accommodations, including tents, plank houses, schools, and sack houses, with over 80% expressing concerns regarding security issues within the IDP camps. Consequently, this investigation concludes that the research area grapples with challenges encompassing food insecurity, personal security, criminal activities, fear of crime, poor health, limited educational opportunities, and precarious livelihoods, thereby augmenting vulnerability and diminishing the quality of life experienced by Internally Displaced Persons. Accordingly, the study offers recommendations advocating for comprehensive planning measures targeting IDPs in Abuja with the purpose of enhancing their well-being and overall quality of life.